2012
DOI: 10.1039/c1jm13433g
|View full text |Cite
|
Sign up to set email alerts
|

A facile chemical method to produce superparamagnetic graphene oxide–Fe3O4hybrid composite and its application in the removal of dyes from aqueous solution

Abstract: A superparamagnetic graphene oxide-Fe 3 O 4 hybrid composite (GO-Fe 3 O 4 ) was prepared via a simple and effective chemical method. Amino-functionalized Fe 3 O 4 (NH 2 -Fe 3 O 4 ) particles are firmly deposited on the graphene oxide sheets. The graphene oxide sheets could prevent NH 2 -Fe 3 O 4 particles from agglomeration and enable a good dispersion of these oxide particles. The as-prepared GO-Fe 3 O 4 hybrid composite had a much higher thermal stability than graphene oxide. The amount of NH 2 -Fe 3 O 4 loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
176
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(197 citation statements)
references
References 66 publications
20
176
1
Order By: Relevance
“…The maximum adsorption capacity was attained 109.5 and 98.8 mg g -1 for MB and CR, respectively, at an initial concentration of 20 mg L -1 . The obtained result is comparable with the previous reports (Yao et al 2012;Xie et al 2012). Tables 1 and 2 show the results obtained in this study with those in the previously reported works on adsorption capacities of various adsorbent in aqueous solution for MB.…”
Section: Adsorption Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…The maximum adsorption capacity was attained 109.5 and 98.8 mg g -1 for MB and CR, respectively, at an initial concentration of 20 mg L -1 . The obtained result is comparable with the previous reports (Yao et al 2012;Xie et al 2012). Tables 1 and 2 show the results obtained in this study with those in the previously reported works on adsorption capacities of various adsorbent in aqueous solution for MB.…”
Section: Adsorption Studiessupporting
confidence: 82%
“…The short equilibrium time needed indicates that the hybrid has high adsorption efficiency to remove cationic and anionic dyes from contaminated water. The obtained results are better than the ones reported previously (Yao et al 2012;Xie et al 2012). The adsorption isotherms of MB and CR for the hybrid are shown in Fig.…”
Section: Adsorption Studiescontrasting
confidence: 50%
See 1 more Smart Citation
“…After the adsorption is accomplished, the nanoparticles can be easily separated from the water by the application of a magnetic field. Hao et al [19] showed that the prepared the γ-Fe 2 O 3 @C nano composite (20 nm) was able to remove approximately 80% of the congo red (CR) within 10 min, and the final removal efficiency of CR was up to 96 @C NPs exhibit better performance for negative charged MO, which strongly suggests that the interaction between adsorbent and adsorbate is electrostatic. In summary, the different adsorption behavior together with the magnetic separation provide a simple and versatile strategy toward designing hybrid NPs for a variety of requirements in water pollution treatment.…”
Section: Hybrids Methodsmentioning
confidence: 99%
“…In general, the Fe 3 O 4 /GO (or RGO) nanocomposites can be synthesized by solvothermal, self-assembly with covalent bond, and in-situ chemical coprecipitation methods, and display efficient adsorption performance in the removals of organic dyes and inorganic metal ions in wastewater [19,[23][24][25][26][27]. The abundant oxygen-containing groups on GO enable a hydrogen bond and electrostatic interactions with organic adsorbates, while the hydrophobic polyaromatic islands of unoxidized benzene rings of RGO offer hydrophobic interaction and π-π stacks toward the organic molecules, especially conjugation molecules.…”
Section: Introductionmentioning
confidence: 99%